Economic reforms and rural development in India - Parthasarathy, G.; Nancharaiah, Gummadi; Academic Foundation (New Delhi, India) (New Delhi : Academic Foundation, 2003)
The book rigorously analysed the pros and cons of structural adjustment and libralisation policies and empirically examined its effects on rural development at national and state level, in terms of agricultural growth, employment opportunities, wages and reduction in rural poverty.
Includes statistical tables.
Includes bibliographical references.
osc 12/07/16
Loans
Keywords: Rural development; Structural adjustment (Economic policy); India